Pengaruh Profitabilitas, Ukuran Perusahaan, Leverage, Good Corporate Governance, dan Kualitas Audit Terhadap Manajemen Laba - Marcella Aulia Dewi; Erma Setiawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of profitability, company size, leverage, good corporate governance, and audit quality on earnings management. The subjects of this study were basic materials manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This study employed a quantitative approach. The sampling technique used purposive sampling, resulting in 20 companies, out of which 100 samples met the criteria. The data used were secondary data obtained from the companies' annual reports. The data analysis method used multiple linear regression analysis. The results indicate that profitability and audit quality influence earnings management, while company size, leverage, and good corporate governance do not.